The performance of masculinity by the "artist": explored in selected works by Peet Pienaar and Robin Rhode - Buch, Sean (My University, 2012)
This body of research centres around the notion of masculinity as performed and socially constructed. The study of masculinity is an ever broadening field and highly relevant to South African social discourse as patriarchy and masculinity are often problematised in reIation to the countries social challenges - specifically violence, rape and abuse which are for the most part perpetrated by men. I have chosen the work of two South African artists with which to engage with the performance and construction of masculintiy. The artists I have selected are Peet Pienaar and Robin Rhode. They are from diverse socio-cultural backgrounds and were selected to give scope to the research as well as for the nature of their work. Both Pienaar and Rhode use their art negotiate and play their masculine identities and in doing so offer new ways to interpret and engage masculinity as a construct and a part of male identity. Because of the so called ‘crisis of masculinity’ that is said to be occurring in contemporary society, many South African scholars have taken up the cause to explore male identity and masculinity, hoping to inform men about the roles they play within society. In this body of research I intend to add to the discourse by exploring the importance of art as a means with which to navigate this complex social landscape